Emosi sebagai Strategi: Popular Culture, Autentisitas Pemasaran Digital “Telisik Lagi” Danilla Riyadi - As Safa Prasodjo; Ignatius Haryanto Djoewanto; Rony Agustino Siahaan (UPT Publikasi Ilmiah Unisba, 2026)
Abstract.This study analyzes the digital marketing strategy of Danilla Riyadi’s album Telisik Lagi through her Instagram account, @danillariyadi, focusing on the role of emotion and elements of popular culture in building audience engagement. This study employs a qualitative approach using textual analysis of five Instagram posts purposively selected from the pre-release to post-release periods of the album. The AIDA model is used as an analytical framework to identify the dynamics of audience engagement, enriched through an analysis of visual, textual, and interactional dimensions, including audience comments. The findings show that the promotional strategy for Telisik Lagi prioritizes emotional connection, nostalgia, collective memory, and relational closeness over hard-selling calls to action. The interaction between Danilla and her audience demonstrates that authenticity and emotional engagement can establish continuity between previous works, new works, and the audience’s personal experiences. The findings indicate that affective engagement and cultural proximity can serve as important components of a promotional strategy for maintaining audience loyalty Abstrak. Penelitian ini menganalisis strategi pemasaran digital album Telisik Lagi karya Danilla Riyadi melalui akun Instagram @danillariyadi, dengan fokus pada peran emosi dan elemen popular culture dalam membangun audience engagement. Penelitian ini menggunakan pendekatan kualitatif dengan metode analisis tekstual terhadap lima unggahan Instagram yang dipilih secara purposif dari periode pra-rilis, hingga pasca-rilis album. Model AIDA digunakan sebagai kerangka analitis untuk mengidentifikasi dinamika keterlibatan audiens, yang diperkaya melalui analisis terhadap elemen visual, tekstual, dan interaksional komentar audiens. Hasil penelitian menunjukkan bahwa strategi promosi Telisik Lagi lebih mengutamakan hubungan emosional, nostalgia, memori kolektif, dan kedekatan relasional dibandingkan ajakan bertindak seperti pendekatan hard selling. Interaksi antara Danilla dan audiens memperlihatkan bahwa autentisitas dan emotional engagement dapat membangun kesinambungan hubungan antara karya terdahulu, karya yang baru, dan pengalaman personal audiens. Temuan menunjukkan keterlibatan afektif dan kedekatan kultural dapat menjadi bagian penting strategi promosi dalam mempertahankan loyalitas audiens.